Faktor-Faktor Penting Dalam Merancang Program Pendidikan Luar Sekolah Untuk Anak Jalanan dan Pekerja Anak - Ajisuksmo, Clara R.P. (UI Scholars Hub, 2012)
Due to poverty, children have to be on the street or involve in child labour to support the families’ economy to survive. As a consequence, children have to drop their school activities out. Refering to article 28 of the Convention of The Rights of The Children (CRC) children have the right to education and the states party recognizes to achieving this right by providing primary education compulsory and available free on the basis to equal opportunity. Non formal education is an alternative education for street children and working children, intended for them to fulfill their right to education. The aim of this study is to identify important factors that are essential for designing and implementing educational program for out-of school children, such as street children and working children. In addition, this study is intended to identify training needs for tutors who facilitate street children and working children in their non formal education program. In order to achieve the research objectives, series of FGDs and in depth interviews with staff of NGO working with out-of school children, tutors who facilitate children’s learning processes, and street children and working children as the beneficiaries of the non-formal education program implemented by the NGO.